A Qualitative Study on Justice and Fairness Perception Through Kohlberg's Theory using Video Games - Tony Wibowo; Deli Deli; Hanita Hanita (Journal of Information System Research (JOSH), 2025)
This study explores how narrative-driven video games can enhance adolescents' moral reasoning, focusing on justice and fairness through Kohlberg’s moral development theory. Addressing the challenge of fostering advanced moral reasoning in youth, it highlights the limitations of traditional methods and the potential of video games to immerse players in ethical dilemmas. Using a qualitative approach, 35 adolescents played a story-based video game and participated in interviews and group discussions. Thematic analysis revealed that 60% began with pre-conventional reasoning, emphasizing individual rewards, but many advanced to conventional reasoning (Stage 4) after gameplay. A smaller group (15%) demonstrated post-conventional reasoning (Stage 5), considering fairness and abstract principles. While 40% found moral options confusing, 11.43% formed emotional connections with the narrative, underscoring the role of storytelling in fostering empathy and reflection. The findings suggest that thoughtfully designed video games can bridge gaps in moral education, offering engaging contexts for ethical exploration. This research supports integrating such games into curricula to enhance moral and cognitive growth in adolescents.